Coronavirus Disease and its Impact on Virtual Education: A Review (Bangladesh Journal of Infectious Diseases, 2022)
A novel coronavirus named Covid-19 spread worldwide from China which disrupted global interaction with the countries, thus closing different regions and borders. This impacted all the sectors. This review briefed the virtual teaching system during pandemic situation and challenges of this teaching system. In academia sector, efforts are required by educational communities to adopt virtual learning and training practices with continuous hygienic practices. This type of virtual learning environment increases communication and interpersonal skills in society. As compared to theoretical studies, virtual education gives students a profound learning experience enabling students to feel connected and engaged to the learning strategies. Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S58-S60